Oxygen therapies and their effects on wound healing - de Smet, Gijs H.J.; Kroese, Leonard F.; Menon, Anand G.; Jeekel, Johannes; van Pelt, Antoon W.J.; Kleinrensink, Gert‐Jan; Lange, Johan F. (Wound repair and regeneration, 2017)
Oxygen is an important factor for wound healing. Although several different therapies investigated the use of oxygen to aid wound healing, the results of these studies are not unequivocal. This systematic review summarizes the clinical and experimental studies regarding different oxygen therapies for promoting wound healing, and evaluates the outcomes according the methodological details. A systematic literature search was conducted using Embase, Medline, Web of Science, Cochrane, PubMed publisher, and Google Scholar libraries. Clinical and experimental studies investigating oxygen for wound healing were selected. Included articles were categorized according to the kind of therapy, study design, and wound type. The methodological details were extracted and analyzed. Sixty‐five articles were identified and divided in three different oxygen therapies: Local oxygen therapy, hyperbaric oxygen therapy, and supplemental inspired oxygen therapy. More than half of the included local oxygen and hyperbaric oxygen studies had one or more significant positive outcomes, 77 and 63%, respectively. Supplemental inspired oxygen therapy during gastrointestinal and vascular surgery was more likely to have a positive result than during other surgical interventions reducing surgical site infections. These many positive outcomes promote the use of oxygen treatment in the stimulation of wound healing. However, the lack of clinical studies and vast methodological diversity made it impossible to perform a proper comparison within and between the different therapies. Further randomized clinical studies are warranted to examine the value of these therapies, especially studies that investigate the more patient‐friendly oxygen dressings and topical wound oxygen therapies. Also, to achieve more solid and consistent data, studies should use more standardized methods and subjects.